HAEMAGGLUTINATION ACTIVITY OF Salmonella typhi FLAGELLIN PROTEIN BASED ON ABO BLOOD GROUP - Ragil Saptaningtyas; Sri Darmawati; Sri Sinto Dewi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Salmonella typhi is a negative basil Gram bacterium that causes typhoid fever. Flagel of S. typhi contain proteins, as locomotor and it can help bacteria to attach on host cells. Haemagglutinin protein is protein that can agglutinate erythrocytes. The goal of this research is to analize S. typhi flagellin proteins haemagglutination activity Based on ABO blood group. Flagellin proteins isolation method of modified Alexan method (2009) and haemagglutination test method of Finkeltein and Hanne method (1982). Haemagglutination result of ABO blood type show that SLT-1 S. typhi flagellin proteins can’t agglutinate human erythrocytes A, B, and O, but it can agglutinate human erythrocytes until 8 times dilution of AB blood type from 50 μg/μl concentration in 50 μl. BA 07.4 S. typhi flagellin proteins can agglutinate human erythrocytes of A blood type until 16 times dilution, 8 times dilution of AB blood type, 4 times dilution of O blood type, and it can’t agglutinate human erythrocytes B blood type.Keywords: Salmonella typhi, Flagellin Proteins, Haemagglutination, Erythrocytes of ABO System.